2022
DOI: 10.1111/pce.14284
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated root phenotypes for improved rice performance under low nitrogen availability

Abstract: Greater nitrogen efficiency would substantially reduce the economic, energy and environmental costs of rice production. We hypothesized that synergistic balancing of the costs and benefits for soil exploration among root architectural phenes is beneficial under suboptimal nitrogen availability. An enhanced implementation of the functional-structural model OpenSimRoot for rice integrated with the ORYZA_v3 crop model was used to evaluate the utility of combinations of root architectural phenes, namely nodal root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 99 publications
0
31
1
Order By: Relevance
“…More research is necessary to characterize rice nodal root types and their function. Although our study suggests a positive relationship between the proportion of the total number of nodal roots classified as 'large‐diameter' and grain yield (via RDW 15–30 cm in the phenotypic correlations and directly by GWAS colocations), this is in contrast to recent results from simulation modelling of rice roots which concluded that a larger proportion of 'small‐diameter' nodal roots was beneficial to plant growth and yield under low‐nitrogen, rainfed direct‐seeded conditions (Ajmera et al, In Press). Therefore, the function of various nodal root class distributions may differ depending on the soil conditions and should be further investigated.…”
Section: Discussioncontrasting
confidence: 69%
“…More research is necessary to characterize rice nodal root types and their function. Although our study suggests a positive relationship between the proportion of the total number of nodal roots classified as 'large‐diameter' and grain yield (via RDW 15–30 cm in the phenotypic correlations and directly by GWAS colocations), this is in contrast to recent results from simulation modelling of rice roots which concluded that a larger proportion of 'small‐diameter' nodal roots was beneficial to plant growth and yield under low‐nitrogen, rainfed direct‐seeded conditions (Ajmera et al, In Press). Therefore, the function of various nodal root class distributions may differ depending on the soil conditions and should be further investigated.…”
Section: Discussioncontrasting
confidence: 69%
“…Root traits can help improve the efficient capture of nutrients like nitrate which is highly mobile in soils. In this issue, combining models for root architecture and for crop performance, Ajmera et al (2022) identified synergistic effect of several root phenes in rice that were linked to better performance under low nitrogen supply. Wacker et al (2022) report how deeper rooting winter wheat varieties exhibit reduced nitrate (N) leaching losses and increase N uptake.…”
Section: Nutrient and Water Acquisition Strategies In High-and Low-in...mentioning
confidence: 99%
“…The actual response greater than, equal to, and less than the expected response respectively corresponds to the synergistic, additive, and antagonistic relationship between the number of cortical cell files and the proportion of aerenchyma formation. More details on this can be found (Ajmera et al, 2022; Ma et al ., 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Exploring the impact of root anatomical phenotypes on soil resource capture is important for informing the development of resource-efficient crop varieties. However, the utility of a phene state depends on the environment as well as interactions with other phene states in integrated phenotypes (Ajmera et al ., 2022; Klein et al ., 2020; Rangarajan et al ., 2018). The number of potential combinations involving multiple phene states over multiple environments exceeds the capabilities of empirical research (Rangarajan et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%